The girl-child and absentee mothers in Yejide Kilanko’s Daughters Who Walk This Path and Chinelo Okparanta’s Under the Udala Trees (JOURNAL OF INNOVATIVE RESEARCH IN MANAGEMENT AND HUMANITIES, 2026)
Literature has been an avenue through which the society is viewed. In this paper, a major aspect of the society is portrayed as it examines the issue of absentee mothers and the girl child in Nigerian literature. By means of betrayal trauma theory and attachment theory with the content analysis method, this study through Yejide Kilanko and Chinelo Okparanta’s Daughters Who Walk This Path and Under the Udala Trees examine the impact of pain of betrayal on the girl child and its effect on the society as against previous studies that explored the bildungsroman/womanist approach. This study finds that the authors in their novels address a prominent societal problem and that through their engagements in the novels, they hope to bring about a much needed societal change.
Keywords: Absent mothers, girlchild, maternal absence, identity formation, African Literature